Dural Invasion Predicts the Laterality and Development of Neck Metastases in Esthesioneuroblastoma - Marinelli, John P.; Janus, Jeffrey R.; Van Gompel, Jamie J.; Link, Michael J.; Moore, Eric J.; Van Abel, Kathryn M.; Peck, Brandon W.; Lohse, Christine M.; Price, Daniel L. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Neck metastases in patients with esthesioneuroblastoma (ENB) constitute the most significant predictor of poor long-term survival. Recently, researchers discovered the existence of dural lymphatic channels that drain to the cervical lymph nodes. From this physiologic basis, we hypothesized that patients with ENB who develop dural invasion (DI) would exhibit a proclivity for neck metastases.Design Retrospective review.Setting Tertiary referral center.Participants All patients treated for ENB from January 1, 1994 to December 31, 2015.Main Outcome Measures Incidence, laterality, and recurrence rate of neck metastases by DI status.Results Sixty-one patients were identified (38% female; median age 49, range, 10–80), 34 (56%) of whom had DI and 27 (44%) did not. Of patients with DI, 50% presented with or developed neck disease following treatment compared with just 22% of those without DI (p = 0.026). Bilateral neck disease was more common in patients with DI (11/34, 32%) compared with those without (2/27, 7%) (p = 0.018). Five-year regional recurrence-free survival rates were 88% for those without and 64% for those with DI (p = 0.022). Kadish C patients with DI were more likely to develop regional recurrence when compared with Kadish C without DI and Kadish A/B (p = 0.083). Further, Kadish C patients with DI displayed worse overall survival than Kadish C without DI and Kadish A/B. Kadish D patients displayed the worst overall survival. The difference in overall survival among these four groups was significant (p < 0.001).Conclusion DI by ENB is associated with increased incidence of cervical nodal metastases, bilateral neck disease, worse regional recurrence-free survival, and poorer overall survival. These data support the division of Kadish C by DI status.
Keywords: esthesioneuroblastoma; olfactory neuroblastoma; dural invasion; elective neck treatment; neck metastases